A competição interespecífica explica a distribuição espacial de macrófitas aquáticas em estuários? - Nunes, Laís Samira Correia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Competitive interaction plays an important role in aquatic macrophytes zonation in estuaries. Estuarine regions are marked by stress gradients, especially in relation to salinity due to marine influence. In less stressful areas, the lower salinity ones, the halophytes can be excluded by freshwater plants, which have higher competitive ability. Thus, salt tolerant species have their occurrence limited to the most stressful areas, which are the high salinity areas. In the Itanhaém River Basin Estuary (SP) the emergent aquatic macrophytes Crinum americanum and Spartina alterniflora are distributed along the salinity gradient. The species occupy opposite ends of the gradient and form mixed banks in the intermediate zone. In this study we sought to understand the distribution of these species in the abovementioned region, assessing which abiotic and biotic factors influence their zonation. We tested the hypothesis that S. alterniflora is not established in the less stressful environment occupied by C. americanum due to the competition effect, and that, C. americanum would be intolerant to high salinity. Three study sites were selected according to the presence of the species in the salinity gradient: S. alterniflora monospecific bank in the lower zone (high salinity), C. americanum monospecific bank in the upper zone (low salinity) and mixed bank of the two species in the middle zone (intermediate salinity) of the estuary. For these sites it was determined the sediment salinity, nutrient availability and grain size, besides the riverside slope. In the laboratory, an experiment was realized to evaluate the species growth in monoculture and mixed culture in the same salinity levels of the study sites. Sediment salinity levels in the gradient correspond to 40, 120 and 260 ppm. The intermediate salinity zone has high nutrient availability. The lower salinity zone has more sandy sediment and larger riverside slope. The experimental data showed that...

A interação competitiva tem importante papel na zonação de macrófitas aquáticas em estuários. As regiões estuarinas são marcadas por gradientes de estresse, principalmente em relação à salinidade, devido à influência marinha. Em áreas menos estressantes, ou seja, de menor salinidade, as halófitas podem ser excluídas pelos vegetais de água doce, os quais possuem maior habilidade competitiva. Assim, espécies tolerantes à salinidade têm sua ocorrência limitada à áreas mais estressantes, ou seja, de elevada salinidade. Na região estuarina da bacia do rio Itanhaém (SP) as macrófitas aquáticas emergentes Crinum americanum e Spartina alterniflora estão distribuídas ao longo do gradiente de salinidade. As espécies ocupam extremos opostos do gradiente e formam bancos mistos na zona intermediária. Neste estudo buscou-se compreender a distribuição destas espécies na região acima citada, avaliando quais fatores abióticos e bióticos influenciam sua zonação. Testamos a hipótese de que S. alterniflora não se estabelece no ambiente menos estressante ocupado por C. americanum devido ao efeito da competição, e ainda que, C. americanum apresentaria restrições à elevada salinidade. Três locais de estudo foram selecionados de acordo com a presença das espécies no gradiente de salinidade: banco monoespecífico de S. alterniflora na porção inferior (elevada salinidade), banco monoespecífico de C. americanum na porção superior (baixa salinidade) e banco misto das espécies na porção intermediária (salinidade intermediária) do estuário. Para estes locais foram determinados a salinidade, a disponibilidade de nutrientes e a granulomentria do sedimento, além da declividade da margem. Em laboratório, um experimento foi desenvolvido para avaliar o crescimento em monoculturas e em cultura mista das espécies nos mesmos níveis de salinidade dos locais em estudo. Os níveis de salinidade do sedimento no gradiente...
Keywords: Aquatic ecology; Ecologia aquatica; Plantas - Competição; Estuarios; Gradiente de concentração; Macrófitas aquáticas; Salinidade; Itanhaém, Rio, Bacia (SP)